KEPALA TATA USAHA DALAM PENGELOLAAN LAYANAN ADMINISTRASI (ARSIP) DI LEMBAGA PENDIDIKAN - Muli Prima Aldi; Tika Widiyan; Adam Saleh; Rahmadanni Pohan; Leni Fitrianti (STAI Nurul Falah Airmolek, 2024)
In educational institutions, one of the factors that influences the quality of the educational institution is the performance of the head of administration. Among the duties of the head of administration is managing letters and archives. The Head of Administration plays an important role in managing archives. These archives need to be managed well because every activity in an educational institution is always related to archives. Archives have an important role in the process of presenting data to leaders in making decisions and formulating policies, therefore in order to present complete, fast and correct information there must be good work systems and procedures in the field of archives